ISLAMIC BOARDING SCHOOL AND FORMAL SCHOOL CURRICULUM INTEGRATION MANAGEMENT IN STRENGTHENING ISLAMIC RELIGIOUS EDUCATION COMPETENCY AT IBS AL FIKRA - M. Luqmanul Haqim; Muhammad Khoiruddin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
In the current educational era, the dichotomy between general sciences and religious studies, coupled with the limited time allocation for Islamic Religious Education (PAI) within the formal curriculum of boarding schools, necessitates strategic intervention. Consequently, this study aims to analyze the management of curriculum integration between the pesantren and formal school systems through the Madin Night Class program at IBS Al Fikra in strengthening students' PAI competencies. The research methodology employed is library research with a qualitative approach. Data were collected through documentation studies of the curriculum, syllabi, and activity schedules, which were subsequently analyzed using the content analysis technique. The findings indicate that IBS Al Fikra implements a systematic managerial strategy encompassing needs-analysis-based planning, curriculum mapping between formal Learning Outcomes (CP) and classical Islamic texts (Kitab Kuning), the technical execution of evening instruction, and evaluation via the imtihan system. This strategy is proven effective in bridging competency gaps across the cognitive, affective, and psychomotor domains. The novelty of this research lies in the utilization of the "night class" instrument as a managerial solution to address curricular hour shortages, thereby achieving graduate competency standards that exceed national requirements. This program successfully synergizes general intellectual intelligence with holistic religious spiritual depth.